PENGUATAN LITERASI BAGI SANTRI DAN IKATAN PELAJAR DI SALATIGA SEBAGAI UPAYA MENYEBARLUASKAN IDE DAN GAGASAN MODERASI BERAGAMA - Bakhrul Amal; Syafawi Ahmad Qadzafi (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Religious radicalism had become a significant challenge to social cohesion, tolerance, and religious harmony in Indonesia. Islamic boarding schools and students held a strategic position in countering extremist narratives through the strengthening of critical and contextual literacy. This community service program aimed to enhance the literacy capacity of students in promoting religious moderation through narrative writing based on local experiences in Salatiga City. The program employed an Asset-Based Community Development approach that emphasized existing social, cultural, and intellectual assets within the Islamic boarding school community. The activities were implemented through needs assessment, literacy and religious moderation workshops, and structured writing training accompanied by mentoring and feedback sessions. The results indicated the emergence of a writing culture among students, increased ability to articulate experiences of religious moderation, and the production of a compiled book of student writings as a tangible outcome. This program contributed to the development of counter-narratives against radicalism and strengthened the role of students as agents of inclusive, dialogical, and moderate Islamic discourse in the public sphere.